Cryptographic Hardware and Embedded Systems - CHES 2013 15th International Workshop, Santa Barbara, CA, USA, August 20-23, 2013. Proceedings - Bertoni, Guido.; Coron, Jean-Sb̌astien. (Lecture Notes in Computer Science,, 2013)
This book constitutes the proceedings of the 15th International Workshop on Cryptographic Hardware and Embedded Systems, CHES 2013, held in Santa Barbara, CA, USA, in August 2013. The 27 papers presented were carefully reviewed and selected from 132 submissions. The papers are organized in the following topical sections: side-channel attacks; physical unclonable function; lightweight cryptography; hardware implementations and fault attacks; efficient and secure implementations; elliptic curve cryptography; masking; side-channel attacks and countermeasures.